Peningkatan Kesejahteraan Petani melalui Program Agroforestri Sengon, Jagung dan Kopi di Desa Gunungsari, Kabupaten Kebumen - Friska Dyah Safitri; Mariyoto Danang Pambudi; Amnan Haris (Universitas Negeri Semarang, 2023)
Agroforestry farming systems can be used to optimize agricultural yields while preserving nature, such as increasing soil fertility and controlling erosion. The agroforestry program is important to implement in the upstream area of the Lukulo watershed, one of which is in Gunungsari Village, Kebumen Regency. Methods of data collection is done by questionnaires, interviews, and observation. Planning for planting begins with socialization of activities and is carried out in a participatory manner by involving the community in planning and implementation. Based on the socialization of the program and collecting data on farmers' interests, the result was that all farmers (24 people in total) were interested in participating in the agroforestry program. Based on the results of discussions with participants, the types of plants most in demand were sengon, corn and coffee. The results of the implementation of participatory socialization and land data collection showed that the Gunungsari Village community was willing to carry out planting using the agroforestry model. Land data collection was carried out by visiting farmers' fields to find out land conditions such as land cover area, land form, access to land, taking coordinates and documentation and attaching a barcode to the registered land. Trees4Trees provides planting socialization and training to participating farmers to explain good and correct planting methods, so that 100% of participants are interested in the agroforestry program.